The Relationship of Nurse's Knowledge Level Towards Compliance with SOP of Post Radial Sheath Revocation Post Heart Catherization - Fauzan, Alief; Wulandari, Shenda Maulina; Sutandi, Aan; Rahmawati, Apriana (Journal of Nursing and Midwifery Sciences, 2022)
Coronary heart disease (CHD) is a condition in which the coronary arteries are narrowed, blocked, or abnormal in the coronary arteries. One of the measures to diagnose CHD is cardiac catheterization (Coronary Angiography), which is an invasive diagnostic procedure using access called sheath. Knowledge of Standard Operating Procedures (SOP) for post-sheath removal after cardiac catheterization is very important. Knowledge is considered one of the factors that can affect the success rate of post-radial sheath removal treatment. The purpose of this study was to determine the relationship between the level of knowledge of nurses and adherence to SOPs for post-radial sheath removal after cardiac catheterization in the cardiac care room at Tarakan Hospital, Jakarta. The study used an analytic observation method with a cross-sectional approach. The research subjects were all nurses in the heart care room at Tarakan Hospital. Samples were taken with a total sampling of 30 respondents. Data collection was carried out using a questionnaire. Correlation test using Kendall-Tau, the correlation between the two variables is 0.010 while the sig (2-tailed) number is 0.17 > greater than a = 0.05, meaning that it can be concluded that there is a relationship between the level of knowledge of nurses and adherence to SOPs for post-revocation care. radial sheath after cardiac catheterization in the cardiac care room at Tarakan Hospital, Jakarta.